ROLE OF CT SIMULATION IN RADIATION THERAPY PLANNING - SR Mahdavi, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Radiotherapy treatment planning (TP) is strongly dependent to the internal organs localizations and inhomogeneity dosimetric corrections based on computerized tomographic scanning (CTS) data. The purpose of this study was to compare the dose distribution parameters between CT-based corrected and non-corrected treatment plans for inhomogeneities within the irradiated volume.METHODS: Fifty three cases of head and neck, pelvis, abdomen and breast cancer were included in this project. All of them were imaged with same CTS machine. Each case was planned twice, one before and one after inhomogeneity CT-based correction with a two dimensional TP system. Statistical analysis was done after calculation the parameters of dose uniformity (Te), average (Davg), minimum (Dmin) and maximum (Dmax) doses for target volume (TV) and organs at risk (OAR). FINDINGS: Briefly, the ratios of mean differences of dosimetric parameter between before and after correction plans to the mean of same parameter after correction were obtained. Mean differences of Te, Davg, Dmin and Dmax for pelvis were -1.59% (p=0.30), -0.993 (p=0.5), -0.890% (p=0.91), 1.29% (p=0.05), respectively. Same parameters for head and neck region were 0%(p=0.5), 0.012(p=0.05), 0%(p=0.99) and 0%(p=1.00) and for chest wall treatment were 7.13%(p<0.001), 4.65%(p=0.04), 1.79%(p=0.37) and -1.61%(p=0.10), respectivelyCONCLUSION: Findings further confirm the positive effect of density correction in chest wall irradiation. Unexpectedly, minimum differences were in head and neck region which can be due to low and high density tissues compensation. Present study has shown the unique and effective application of CTS data for dosimetric error corrections rather than internal organ localizations. If not considered, the dosimetry deviations will be out of tolerance doses according to the limits defined by standard organizations (±5%) for tumors and normal tissues as well.